Reliable Cooperative Spectrum Sensing Algorithm Based on Dempster-Shafer Theory - Jing Li; Jian Liu; Keping Long (2010 IEEE Global Telecommunications Conference GLOBECOM 2010, 2010)
Cooperative spectrum sensing for cognitive radio is recently being studied to minimize uncertainty in primary user detection. In order to improve the detection probability under a sustainable false alarm probability, a reliable scheme for cooperative spectrum sensing based on double threshold energy detection and Dempster-Shafer (D-S) theory is proposed in this paper. In the algorithm, the double threshold method is used to calculate the local spectrum sensing requirements, which is more accurate than using a single threshold. The D-S theory, which is similar to human reasoning, is adopted to combine different sensing decisions from each cognitive user. A final decision is then made in the fusion center, which decides whether the primary user is present or not. To reduce the redundant nodes, we propose the use of node selection. The analytical results match very well with the simulation results. Simulation results show that the reliability of decision is improved due to the accurate calculation of the local sensing information.